2023
DOI: 10.1186/s12885-023-10942-y
|View full text |Cite
|
Sign up to set email alerts
|

Biliary-enteric reconstruction in laparoscopic radical resection of hilar cholangiocarcinoma: a single-center retrospective cohort study

Abstract: Objective To evaluate the feasibility and quality of biliary-enteric reconstruction (BER) in laparoscopic radical resection of hilar cholangiocarcinoma (LsRRH) versus open surgery and propose technical recommendations. Methods Data of 38 LsRRH and 54 radical laparotomy resections of hilar cholangiocarcinoma (LtRRH) cases were collected from our institution. BER was evaluated via biliary residuals numbers, number of anastomoses, anastomosis manner, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This difficulty may result in postoperative biliary fistula, anastomotic stenosis, and other serious complications. Liu 28 compared BER between laparoscopic and open radical resection for HCCA and found a significant difference in the anastomosis time (65.67 ± 21.53 vs 42.5 ± 19.77 min, P < 0.05) and BER time ratio (15.08 ± 3.64% vs 11.76 ± 2.54%, P < 0 0.05), with longer times observed in the laparoscopic group mainly owing to the complexity of laparoscopic BER procedures. However, in a systematic review, Guerra 29 suggested that robotic surgery has become a treatment option for biliary tract surgery in large clinical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difficulty may result in postoperative biliary fistula, anastomotic stenosis, and other serious complications. Liu 28 compared BER between laparoscopic and open radical resection for HCCA and found a significant difference in the anastomosis time (65.67 ± 21.53 vs 42.5 ± 19.77 min, P < 0.05) and BER time ratio (15.08 ± 3.64% vs 11.76 ± 2.54%, P < 0 0.05), with longer times observed in the laparoscopic group mainly owing to the complexity of laparoscopic BER procedures. However, in a systematic review, Guerra 29 suggested that robotic surgery has become a treatment option for biliary tract surgery in large clinical centers.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research exists on robot-assisted Roux-en-Y hepaticojejunostomy. 28 , 30 , 31 . In this study, a mesentery with fewer blood vessels was selected for appropriate cutting to ensure that the raised intestinal loop had sufficient length.…”
Section: Discussionmentioning
confidence: 99%